Method Improving for Isolation and Characterization of Allergy-Inducing Polymer Impurities in Cefotaxime Sodium Medicines Available From Pharmaceutical Industry - Fu, Yanan; Li, Jin; Feng, Fang; Yin, Lihui (Frontiers in Chemistry, 2022)
Objective: To prepare and validate the chemical structure of the cefotaxime dimer and cefotaxime trimer impurities available from pharmaceutical industry. Methods: A polymer stock solution of cefotaxime sodium was obtained using a concentrated solution degradation method. The cefotaxime dimer and trimer impurities were separated and purified by preparative reversed-high-performance liquid chromatograph (RP-HPLC), and the pure cefotaxime dimer and trimer were obtained by a freeze-drying method. The two impurities were characterized by infrared (IR) spectroscopy, ultraviolet (UV) spectroscopy, mass spectroscopy, and nuclear magnetic resonance (NMR, including one-dimensional and two-dimensional NMR). The groups corresponding to the characteristic absorption peaks in the UV and IR spectra were analyzed, and the 1H and 13C NMR signals were assigned. Results: The cefotaxime dimer was isolated and purified from the actual sample of industrial medicines, and chemical structure of the dimer is the same as in the dimers investigated earlier. The polymerization sites and stereoscopic configuration of trimer impurity was validated for the first time. Conclusion: This study is of great significance for the study of the structures and quality control of polymer impurities in cephalosporin drugs. Promoting the polymerization sites study and providing a technical basis for allergic study of polymer impurities.